PENINGKATAN KINERJA GURU MELALUI SUPERVISI AKADEMIK DI SD INPRES KAMALAPUTI - DORKAS KONDANAMU (ACADEMIA: Jurnal Inovasi Riset Akademik, 2023)
The principal as a learning leader has an important role in improving teacher performance to achieve the expected learning objectives. The principal as a supervisor provides assistance through supervision activities to improve the learning process. This research activity was carried out in two cycles with the result that there was an increase in value between cycle 1 and cycle 2, both lesson plans or lesson plans and the learning process in the classroom during the observation process. These results were obtained due to implementing supervision by examining learning tools related to the preparation of lesson plans, preparing media and learning resources while providing assistance according to teacher needs, this was done at the first meeting. The activities at the second meeting were carried out by academic supervision with individual techniques. Not only that, the principal had private conversations regarding the preparations and steps prepared in the process of implementing teaching and learning activities including in the preparation of visual aids and the implementation of evaluations included in the learning process. The results in implementing these actions can be seen in cycle 2 which describes all teachers or 17 out of 17 teachers or 100% of teachers who have completed both the preparation of learning tools and the observation of the learning process with scores between 76 – 100. ABSTRAKKepala sekolah sebagai pemimpin pembelajaran memiliki peran penting dalam meningkatkan kinerja guru untuk tercapainya tujuan pembelajaran yang diharapkan. Kepala sekolah sebagai supervisor melakukan pendampingan melalui kegiatan supervisi untuk memperbaiki proses pembelajaran. Kegiatan penelitian ini dilakukan dalam dua siklus dengan hasil terjadi peningkatan nilai antara siklus 1 dengan siklus 2 baik itu perencanaan pembelajaran atau RPP maupun proses pembelajaran di dalam kelas pada saat proses pengamatan berlangsung. Hasil tersebut diperoleh karena menerapkan supervisi dengan menelaah instrumen perangkat pembelajaran terkait penyusunan RPP, persiapan media dan sumber belajar sekaligus memberikan pendampingan sesuai kebutuhan guru hal ini dilakukan pada pertemuan pertama. Adapun kegiatan pada pertemuan kedua dilakukan supervisi akademik dengan teknik individu. Tidak hanya itu, kepala sekolah melakukan percakapan pribadi terkait persiapan dan langkah-langkah yang disiapkan dalam proses pelaksanaan kegiatan belajar mengajar termasuk dalam persiapan alat peraga dan pelaksanaan evaluasi yang terinklud dalam proses pembelajaran. Hasil dalam menerapkan tindakan tersebut dapat dilihat pada siklus 2 yang menggambarkan semua guru atau 17 dari 17 guru atau 100% guru sudah tuntas, baik pada penyusunan perangkat pembelajaran maupun pada pengamatan proses pembelajaran dengan perolehan nilai diantara 76 – 100.